Satiation and Stress-Induced Hypophagia: Examining the Role of Hindbrain Neurons Expressing Prolactin-Releasing Peptide or Glucagon-Like Peptide 1 - Maniscalco, James W.; Kreisler, Alison D.; Rinaman, Linda (Frontiers in Neuroscience, 2013)
Neural circuits distributed within the brainstem, hypothalamus, and limbic forebrain interact to control food intake and energy balance under normal day-to-day conditions, and in response to stressful conditions under which homeostasis is threatened. Experimental studies using rats and mice have generated a voluminous literature regarding the functional organization of circuits that inhibit food intake in response to satiety signals, and in response to stress. Although the central neural bases of satiation and stress-induced hypophagia often are studied and discussed as if they were distinct, we propose that both behavioral states are generated, at least in part, by recruitment of two separate but intermingled groups of caudal hindbrain neurons. One group comprises a subpopulation of noradrenergic (NA) neurons within the caudal nucleus of the solitary tract (cNST; A2 cell group) that is immunopositive for prolactin-releasing peptide (PrRP). The second group comprises non-adrenergic neurons within the cNST and nearby reticular formation that synthesize glucagon-like peptide 1 (GLP-1). Axonal projections from PrRP and GLP-1 neurons target distributed brainstem and forebrain regions that shape behavioral, autonomic, and endocrine responses to actual or anticipated homeostatic challenge, including the challenge of food intake. Evidence reviewed in this article supports the view that hindbrain PrRP and GLP-1 neurons contribute importantly to satiation and stress-induced hypophagia by modulating the activity of caudal brainstem circuits that control food intake. Hindbrain PrRP and GLP-1 neurons also engage hypothalamic and limbic forebrain networks that drive parallel behavioral and endocrine functions related to food intake and homeostatic challenge, and modulate conditioned and motivational aspects of food intake.